2007 IEEE International Geoscience and Remote Sensing Symposium 2007
DOI: 10.1109/igarss.2007.4423943
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and spatial classification of hyperspectral data using SVMs and morphological profiles

Abstract: Abstract-A method is proposed for the classification of urban hyperspectral data with high spatial resolution. The approach is an extension of previous approaches and uses both the spatial and spectral information for classification. One previous approach is based on using several principal components from the hyperspectral data and building several morphological profiles. These profiles can be used all together in one extended morphological profile. A shortcoming of that approach is that it was primarily desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
247
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(252 citation statements)
references
References 9 publications
1
247
0
4
Order By: Relevance
“…Regarding the possibilities to extend the originally binary SVMs to multiclass settings, there has been quite some research recently [31], and architectures like 1vs1 and 1vsALL are widely used nowadays (see [32]- [34] for comparisons). The 1vs1 and 1vsALL SVM architectures are widely used in remote sensing applications [35]- [37].…”
Section: Multiclass Svms With Soft Answersmentioning
confidence: 99%
“…Regarding the possibilities to extend the originally binary SVMs to multiclass settings, there has been quite some research recently [31], and architectures like 1vs1 and 1vsALL are widely used nowadays (see [32]- [34] for comparisons). The 1vs1 and 1vsALL SVM architectures are widely used in remote sensing applications [35]- [37].…”
Section: Multiclass Svms With Soft Answersmentioning
confidence: 99%
“…Previous researches have shown that mathematical morphology operators as opening and closing by reconstruction help us to set up spatial information in analysis [6]. Our approach also utilizes mathematical morphology to yield a nonlinear decomposition presented in Section 3.…”
Section: Reduction and Classificationmentioning
confidence: 99%
“…[12] use improved classification of pixel level and object level remote sensing images to distinguish different objects. In view of the special form of urban objects, people also put forward some spatial characteristics calculation methods, such as pixel shape index (PSI) [13], morphological sequence [14][15][16][17], and multiscale urban complexity index(MUCI) based on wavelet texture [14,15]. In order to enhance the efficiency of automatic extraction of buildings, some new methods have been proposed [17][18][19][20][21].…”
Section: Introducementioning
confidence: 99%